Estrutura de assembleias de aves em paisagens do ecótono Amazônia-Cerrado - Tavares, Gabriel Magalhães (2023)
The Amazon rainforest is the largest tropical forest in the world, and the cerrado is the most biodiverse savanna on the planet. The transition zone between these two biomes presents unique characteristics, harboring a potentially greater biological diversity than the adjacent areas. However, this region has been severely impacted by deforestation, especially in the state of Mato Grosso, Brazil. Understanding how the amount of available habitat in a landscape influences the dynamics of biological communities is crucial for understanding the effects of deforestation. In this study, we aimed to conduct an inventory and investigate the structure of bird assemblages in a region of Amazon-Cerrado ecotone in three sub-basins of the Teles Pires river basin, located in Mato Grosso, Brazil. In the first chapter of this study, we conducted an inventory of the avifauna in the region. For the bird inventory, we used the MacKinnon Lists methodology, supplemented by citizen science data. The results revealed that the region still harbors a rich and diverse bird community, with a total of 569 recorded species, including threatened and endemic species from both the Amazon and the Cerrado, highlighting the importance of this region for bird conservation. In the second chapter, we aimed to analyze the structure of the assemblages in the three sub-basins. We observed that species richness was similar among the sub-basins, but species abundance and composition varied significantly among them, indicating possible differences in environmental conditions and deforestation pressure. Furthermore, we found that frugivorous birds were the most affected trophic guild by habitat loss processes, suggesting the importance of food resource availability for maintaining bird communities in the study region. Another relevant finding was that bird assemblages inhabiting the interior of fragmented areas were more negatively affected by fragmentation and habitat loss compared to assemblages occurring at the edges of these areas. This may indicate that interior areas are facing greater environmental pressures and experiencing more intense effects of fragmentation, which can have important consequences for bird conservation. In summary, our results highlight the importance of the Amazon-Cerrado ecotone region for bird conservation, demonstrating the richness and diversity of species in this area. Moreover, our findings underscore the negative effects of habitat loss and fragmentation on bird assemblages, particularly on the most sensitive trophic guilds, and provide important insights for understanding ecological processes occurring in this region, thus contributing to the development of effective strategies for biodiversity conservation.